TRANSLATION FEATURES OF EMERGENCY TERMS IN ENGLISH AND UZBEK: A COMPARATIVE ANALYSIS - Badalbayeva, Maloxat (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
Translation of emergency terms is a crucial aspect of effective communication, especially in life-threatening situations where quick and accurate understanding of information is vital. This article explores the specific features of translating emergency terms from English into Uzbek and vice versa. It focuses on the linguistic, cultural, and practical challenges involved in the process. Special attention is given to terminological equivalence, morphological structures, and the impact of different socio-linguistic contexts on the interpretation of terms in emergency-related fields such as healthcare, disaster response, and law enforcement.